Digital Gaming Participation from a Serious Leisure Perspective Examining Digital Literacy and Mindful Attention Awareness Levels - Cengiz, Recep; Er, Batuhan (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
The aim of this study is to examine the relationship between digital game participation, digital literacy and mindful attention awareness levels from a serious leisure perspective. The study utilized the relational screening model, one of the quantitative research methods. The demographic information form, Digital Literacy Scale, Mindful Attention Awareness Scale and Serious Leisure Scale prepared by the researchers were used as data collection tools. The sample group of the study consists of 171 females (%36.3) and 300 males (%63.7) with an average age of 24.71±8.434. When the findings of the study are examined, no significant difference was found in terms of serious leisure seriousness, personal benefit and social benefit sub-dimensions, digital literacy and mindful attention awareness in terms of gender variable. While significant differences were found in terms of serious leisure and digital literacy levels in terms of weekly participation frequency in digital games, no significant difference was found in terms of conscious awareness level. While a difference was found in terms of serious leisure and digital literacy levels in terms of daily participation duration in digital games, no significant difference was found in mindful attention awareness level. The results show that there is a relationship between serious leisure, digital literacy and mindful attention awareness. However, digital literacy is a predictor of serious leisure and mindful attention awareness level. In addition, mindful attention awareness level is a predictor of serious leisure social benefit dimension.